Modernization of Islamic Education in Indonesia: An Analysis of Malik Fadjar's Thoughts - Fawziyah Tansyah Siregar; Rusydi Ananda; Ali Imran Sinaga (Newinera Publisher, 2026)
This study examines the modernization of Islamic education in Indonesia through an analysis of the educational thought of Malik Fadjar. Employing a qualitative approach with a figure-based study design, the research explores Malik Fadjar’s ideas and practical contributions to educational reform, particularly in the areas of human resource development, curriculum modernization, and institutional governance. Data were collected through in-depth interviews, observation, and documentary analysis, and analyzed using thematic content analysis. The findings reveal that Malik Fadjar conceptualized modernization as a holistic and integrative process aimed at overcoming the dichotomy between religious and general knowledge while preserving Islamic values. His reform agenda emphasizes ethical leadership, teacher professionalism, curriculum integration, and participatory governance as key pillars of sustainable educational development. The study further demonstrates that Malik Fadjar’s ideas remain highly relevant in addressing contemporary challenges faced by Islamic education, including globalization, technological change, and institutional competitiveness. This research contributes to the discourse on Islamic education reform by highlighting a value-based modernization model that harmonizes tradition and modernity within the Indonesian educational context.